Pengaruh Job Embeddedness, Stres Kerja Dan Kepuasan Kerja Terhadap Turnover Intention Studi Pada Karyawan Gembira Loka Zoo Yogyakarta - Muhammad Fahmi Syaefudin; Prayekti Prayekti (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2020)
The purpose of this study is to analyze (1) Job Embeddedness on Turnover Intention, (2) Job Stress on Turnover Intention, (3) Job Satisfaction on Turnover Intention.This research is a quantitative study with a sample of 42 respondents in Gembira Loka Zoo Yogyakarta employees. The technique used in sampling uses accindental sampling and data collection is done using questionnaire media. The analytical tool used is multiple linear regression with the help of SPSS 23 software.The results of this study indicate that (1) Job Embeddedness has a negative and significant effect on Turnover Intention, (2) Job Stress has a positive and significant effect on Turnover Intention, (3) Job Satisfaction has a negative but not significant effect on Turnover Intention.